Revision surgery for instrumentation failure after total en bloc spondylectomy: a retrospective case series - Kazuya Shinmura; Satoshi Kato; Satoru Demura; Noriaki Yokogawa; Noritaka Yonezawa; Takaki Shimizu; Norihiro Oku; Ryo Kitagawa; Makoto Handa; Ryohei Annen; Hideki Murakami; Hiroyuki Tsuchiya (BMC Musculoskeletal Disorders, 2020)
Abstract Background There have been several reports of instrumentation failure after three-column resections such as total en bloc spondylectomy (TES) for spinal tumors; however, clinical outcomes of revision surgery for instrumentation failure after TES are seldom reported. Therefore, this study assessed the clinical outcomes of revision surgery for instrumentation failure after TES. Methods This study employed a retrospective case series in a single center and included 61 patients with spinal tumors who underwent TES between 2010 and 2015 and were followed up for > 2 years. Instrumentation failure rate, back pain, neurological deterioration, ambulatory status, operation time, blood loss, complications, bone fusion after revision surgery, and re-instrumentation failure were assessed. Data were collected on back pain, neurological deterioration, ambulatory status, and management for patients with instrumentation failure, and we documented radiological bone fusion and re-instrumentation failure in cases followed up for > 2 years after revision surgery. Results Of the 61 patients, 26 (42.6%) experienced instrumentation failure at an average of 32 (range, 11–92) months after TES. Of these, 23 underwent revision surgery. The average operation time and intraoperative blood loss were 204 min and 97 ml, respectively. Including the six patients who were unable to walk after instrumentation failure, all patients were able to walk after revision surgery. Perioperative complications of reoperation were surgical site infection (n = 2) and delayed wound healing (n = 1). At the final follow-up, bone fusion was observed in all patients. No re-instrumentation failure was recorded. Conclusion Bone fusion was achieved by revision surgery using the posterior approach alone.